Insecticide seed treatments for managing maggots (Diptera: Anthomyiidae) in onion across selected regions in North America - Leonardo D. Salgado; Alan G. Taylor; Mary Ruth McDonald; Rob G. Wilson; Timothy D. Waters; Josephine B. Antwi; Stuart Reitz; Nathan Hesler; Brian A. Nault (Crop Protection, 2026)

Quantitative microbial risk assessment to evaluate failure assumptions and excess treatment requirements for direct potable reuse - Jeremy M. Wilson; Amos Branch; Daniel Gerrity; Katherine Crank; Andrew Salveson; Stuart J. Khan (Water Research, 2026)

The effectiveness of polarized versus high-intensity training in moderately trained cyclists: a randomized parallel-design study - Andres Moran-MacDonald; Stuart Wilson; Zeyu Wu; Grace Haines; Lucas Beaupre; Joshua Aube; Carter Andrews; Noah Jonsson; Brendon J. Gurd (European Journal of Applied Physiology, 2026)

Wildfire smoke alters observations of 65% of breeding bird species in New York State - Festus O. Adegbola; Stuart M. Evans; Olivia V. Sanderfoot; Adam M. Wilson (Biodiversity and Conservation, 2026)
Smoke from wildfires can be transported hundreds of miles, exposing birds to toxic air across a large geographic area. Yet, research on the impacts of wildfire smoke on wild birds is extremely limited. Quantifying the relationship between wildfire smoke and bird detectability during monitoring surveys is a critical first step in assessing the broader ecological impacts of smoke disturbance. In this study, we evaluate how fine particulate matter (PM 2.5 ), a well-established marker of wildfire smoke and an important air pollutant for public health, influences the probability of observing 84 breeding birds in New York, USA, during the 2021–2023 breeding seasons. We use generalized linear mixed models to relate bird observations from 98,960 eBird checklists to local measurements of ambient PM 2.5 available from ground-based monitors After accounting for habitat, time of day, weather, seasonality, and survey effort, we found that PM 2.5 affected the probability of observing nearly 70% of study species. Across all study species, 18% (15 species) were more likely to be observed and 48% (40 species) were less likely to be observed as PM 2.5 increased. Our findings demonstrate that wildfire smoke influences the probability of observing birds, with species showing divergent responses that may reflect behavioral changes under smoky conditions. Our results support previous research suggesting that wildfire smoke is an important and underexplored component of the detection process; as such, failing to account for air quality may bias models of species distributions and abundance. As climate change continues to escalate global wildfire activity, it is crucial to understand how birds will be affected by increased smoke pollution. Our study provides insights into variation in species responses to smoke exposure, helping inform future research and conservation actions.

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Predicting interactions of sperm and killer whales with longline fisheries in the Southern Ocean: a spatiotemporal modelling approach for conflict mitigation in the Crozet and Kerguelen Archipelagos - Margaux Mollier; Christophe Guinet; Clara Péron; Félix Massiot-Granier; Nicolas Gasco; Charlotte Chazeau; Solène Derville; Eloise Wilson; Stuart Corney; Vinicius Robert; Camille Mazé-Lambrechts; Paul Tixier (Biodiversity and Conservation, 2026)

A horizon scan of biological conservation issues for 2026 - William J. Sutherland; Stuart H.M. Butchart; Stewart J. Clarke; Nigel R. Doar; Helen Doran; Imogen C. Douglas; Daniel J. Field; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Hermanni Kaartokallio; et al. (Trends in Ecology & Evolution, 2026)

Managing range-shifting, competing species in marine reserve networks: the importance of reserve configuration and transient dynamics in age-structured populations - Alicia M. Cheripka; Stuart R. Borrett; J. Wilson White (Theoretical Ecology, 2025)

Closed-loop recycling of reclaimed short carbon fibre reinforced polyamide composites - Adrian Lopera-Valle; Peter Wilson; Stuart R. Coles; Kerry Kirwan (Journal of Cleaner Production, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

The diversity, frequency and severity of natural hazard impacts on subsea telecommunications networks - Lucy Bricheno; Isobel Yeo; Michael Clare; James Hunt; Allan Griffiths; Lionel Carter; Peter J. Talling; Megan Baker; Stuart Wilson; Matthew West; Semisi Panuve; Samuiela Fonua (Earth-Science Reviews, 2024)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Rapid remote volcanic ashfall impact assessment for the 2022 eruption of Hunga volcano, Tonga: a bespoke approach and lessons identified - Alana M. Weir; James H. Williams; Thomas M. Wilson; Josh L. Hayes; Carol Stewart; Graham S. Leonard; Christina Magill; Susanna F. Jenkins; Shaun Williams; Heather M. Craig; Taaniela Kula; Stuart Fraser; et al. (Bulletin of Volcanology, 2024)
When disasters occur, rapid impact assessments are required to prioritise response actions, support in-country efforts and inform the mobilisation of aid. The 15 January 2022 eruption of Hunga volcano, Tonga, and the resulting atmospheric shockwave, ashfall, underwater mass disturbance and tsunami, caused substantial impacts across the Kingdom of Tonga. Volcanic impacts on the scale observed after the eruption are rare, necessitating a reliance on international advice and assistance. The situation was complicated by the loss of Tonga’s international submarine fibreoptic cable (causing a complete loss of communications for approximately 20 days) along with border closures due to the COVID-19 pandemic. A need emerged for a rapid remote volcanic impact assessment and provision of specialist advice to help inform the response of international partners. Here we present a novel methodology for conducting rapid remote volcanic ashfall impact assessments, conducted over a 10-day period following the eruption. We used three different hazard models for ashfall thickness across the main island of Tongatapu and available asset information and vulnerability functions for buildings, agriculture, electricity networks, water supply and roads, to provide initial estimates of losses due to ashfall from the 15 January eruption. For buildings, we estimated losses both as total losses and as percentages of the total replacement cost of buildings on Tongatapu. For agriculture, we made probabilistic estimates of production losses for three different crop classes. For ashfall clean-up, we estimated ranges of ashfall volumes requiring clean-up from road surfaces and roofs. For water supply, electricity networks and roads, our analysis was limited to assessing the exposure of important assets to ashfall, as we had insufficient information on system configurations to take the analysis further. Key constraints on our analysis were the limited nature of critical infrastructure asset inventories and the lack of volcanic vulnerability models for tropical regions including Pacific Island nations. Key steps towards iteratively improving rapid remote impact assessments will include developing vulnerability functions for tropical environments as well as ground-truthing estimated losses from remote approaches against in-person impact assessment campaigns.

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Approaching the challenge of multi-phase, multi-hazard volcanic impact assessment through the lens of systemic risk: application to Taranaki Mounga - Alana M. Weir; Thomas M. Wilson; Mark S. Bebbington; Sarah Beaven; Teresa Gordon; Craig Campbell-Smart; Stuart Mead; James H. Williams; Roger Fairclough (Natural Hazards, 2024)
Effective volcanic impact and risk assessment underpins effective volcanic disaster risk management. Yet contemporary volcanic risk assessments face a number of challenges, including delineating hazard and impact sequences, and identifying and quantifying systemic risks. A more holistic approach to impact assessment is required, which incorporates the complex, multi-hazard nature of volcanic eruptions and the dynamic nature of vulnerability before, during and after a volcanic event. Addressing this need requires a multidisciplinary, integrated approach, involving scientists and stakeholders to co-develop decision-support tools that are scientifically credible and operationally relevant to provide a foundation for robust, evidence-based risk reduction decisions. This study presents a dynamic, longitudinal impact assessment framework for multi-phase, multi-hazard volcanic events and applies the framework to interdependent critical infrastructure networks in the Taranaki region of Aotearoa New Zealand, where Taranaki Mounga volcano has a high likelihood of producing a multi-phase explosive eruption within the next 50 years. In the framework, multi-phase scenarios temporally alternate multi-hazard footprints with risk reduction opportunities. Thus, direct and cascading impacts and any risk management actions carry through to the next phase of activity. The framework forms a testbed for more targeted mitigation and response planning and allows the investigation of optimal intervention timing for mitigation strategies during an evolving eruption. Using ‘risk management’ scenarios, we find the timing of mitigation intervention to be crucial in reducing disaster losses associated with volcanic activity. This is particularly apparent in indirect, systemic losses that cascade from direct damage to infrastructure assets. This novel, dynamic impact assessment approach addresses the increasing end-user need for impact-based decision-support tools that inform robust response and resilience planning.

Improving continental hydrological models for future climate conditions via multi-objective optimisation - Wendy Sharples; Ulrike Bende-Michl; Louise Wilson; Ashkan Shokri; Andrew Frost; Stuart Baron-Hay (Environmental Modelling & Software, 2024)

The sustainability of convenience food: A review and design research agenda - Princess Woy; Garrath T. Wilson; Stuart Cockbill (Journal of Cleaner Production, 2024)

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Adapting the CROPGRO Perennial Forage model to predict growth and development of Pensacola bahiagrass - Hunter D. Smith; Chris H. Wilson; Stuart J. Rymph; Erick R.S. Santos; Kenneth J. Boote (Field Crops Research, 2023)

Anthropogenic nitrogen pollution threats and challenges to the health of South Asian coral reefs - Stuart C. Painter; Yuri Artioli; Fathimath Hana Amir; Jessica Arnull; Raja S. Ganeshram; Nizam Ibrahim; V. Deepak Samuel; R.S. Robin; R. Raghuraman; R. Purvaja; R. Ramesh; Arjan Rajasuriya; et al. (Frontiers in Marine Science, 2023)
Nitrogen pollution is a widespread and growing problem in the coastal waters of South Asia yet the ecological impacts on the region’s coral ecosystems are currently poorly known and understood. South Asia hosts just under 7% of global coral reef coverage but has experienced significant and widespread coral loss in recent decades. The extent to which this coral ecosystem decline at the regional scale can be attributed to the multiple threats posed by nitrogen pollution has been largely overlooked in the literature. Here, we assess the evidence for nitrogen pollution impacts on corals in the central Indian Ocean waters of India, Sri Lanka and the Maldives. We find that there is currently limited evidence with which to clearly demonstrate widespread impacts on coral reefs from nitrogen pollution, including from its interactions with other stressors such as seawater warming. However, this does not prove there are no significant impacts, but rather it reflects the paucity of appropriate observations and related understanding of the range of potential impacts of nitrogen pollution at individual, species and ecosystem levels. This situation presents significant research, management and conservation challenges given the wide acceptance that such pollution is problematic. Following from this, we recommend more systematic collection and sharing of robust observations, modelling and experimentation to provide the baseline on which to base prescient pollution control action.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Persistence of a reef fish metapopulation via network connectivity: theory and data - Allison G. Dedrick; Katrina A. Catalano; Michelle R. Stuart; J. Wilson White; Humberto R. Montes; Malin L. Pinsky (Ecology Letters, 2021)
Determining metapopulation persistence requires understanding both demographic rates and patch connectivity. Persistence is well understood in theory but has proved challenging to test empirically for marine and other species with high connectivity that precludes classic colonisation–extinction dynamics. Here, we assessed persistence for a yellowtail anemonefish ( Amphiprion clarkii ) metapopulation using 7 years of annual sampling data along 30 km of coastline. We carefully accounted for uncertainty in demographic rates. Despite stable population abundances through time and sufficient production of surviving offspring for replacement, the pattern of connectivity made the metapopulation unlikely to persist in isolation and reliant on immigrants from outside habitat. To persist in isolation, the metapopulation would need higher fecundity or to retain essentially all recruits produced. This assessment of persistence in a marine metapopulation shows that stable abundance alone does not indicate persistence, emphasising the necessity of assessing both demographic and connectivity processes to understand metapopulation dynamics.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Catalyzing sustainable fisheries management through behavior change interventions - Gavin McDonald; Molly Wilson; Diogo Veríssimo; Rebecca Twohey; Michaela Clemence; Dean Apistar; Stephen Box; Paul Butler; Fel Cesar Cadiz; Stuart J. Campbell; Courtney Cox; Micah Effron; et al. (Conservation Biology, 2020)
Small‐scale fisheries are an important livelihood and primary protein source for coastal communities in many of the poorest regions in the world, yet many are overfished and thus require effective and scalable management solutions. Positive ecological and socioeconomic responses to management typically lag behind immediate costs borne by fishers from fishing pressure reductions necessary for fisheries recovery. These short‐term costs challenge the long‐term success of these interventions. However, social marketing may increase perceptions of management benefits before ecological and socioeconomic benefits are fully realized, driving new social norms and ultimately long‐term sustainable behavior change. By conducting underwater visual surveys to quantify ecological conditions and by conducting household surveys with community members to quantify their perceptions of management support and socioeconomic conditions, we assessed the impact of a standardized small‐scale fisheries management intervention that was implemented across 41 sites in Brazil, Indonesia, and the Philippines. The intervention combines TURF reserves (community‐based territorial use rights for fishing coupled with no‐take marine reserves) with locally tailored social‐marketing behavior change campaigns. Leveraging data across 22 indicators and 4 survey types, along with data from 3 control sites, we found that ecological and socioeconomic impacts varied and that communities supported the intervention and were already changing their fishing practices. These results suggest that communities were developing new social norms and fishing more sustainably before long‐term ecological and socioeconomic benefits of fisheries management materialized.

Rapid larval growth is costly for post-metamorphic thermal performance in a Great Barrier Reef fish - Carmen Rose Burke da Silva; Robbie Stuart Wilson; Cynthia Riginos (Coral Reefs, 2019)

An intertidal fish shows thermal acclimation despite living in a rapidly fluctuating environment - Carmen Rose Burke da Silva; Cynthia Riginos; Robbie Stuart Wilson (Journal of Comparative Physiology B, 2019)

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Differential Morphological and Biochemical Recovery from Chemotherapy-Induced Peripheral Neuropathy Following Paclitaxel, Ixabepilone, or Eribulin Treatment in Mouse Sciatic Nerves - B. M. Cook; K. M. Wozniak; D. A. Proctor; R. B. Bromberg; Y. Wu; B. S. Slusher; B. A. Littlefield; M. A. Jordan; L. Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2018)

Microtubule-Targeting Agents Eribulin and Paclitaxel Differentially Affect Neuronal Cell Bodies in Chemotherapy-Induced Peripheral Neuropathy - Sarah J. Benbow; Krystyna M. Wozniak; Bridget Kulesh; April Savage; Barbara S. Slusher; Bruce A. Littlefield; Mary Ann Jordan; Leslie Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2017)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Effects of Paclitaxel and Eribulin in Mouse Sciatic Nerve: A Microtubule-Based Rationale for the Differential Induction of Chemotherapy-Induced Peripheral Neuropathy - Sarah J. Benbow; Brett M. Cook; Jack Reifert; Krystyna M. Wozniak; Barbara S. Slusher; Bruce A. Littlefield; Leslie Wilson; Mary Ann Jordan; Stuart C. Feinstein (Neurotoxicity Research, 2016)

Measuring coral size-frequency distribution using stereo video technology, a comparison with in situ measurements - Joseph A. Turner; Nicholas V. C. Polunin; Stuart N. Field; Shaun K. Wilson (Environmental Monitoring and Assessment, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

Experimental evidence that invasive grasses use allelopathic biochemicals as a potential mechanism for invasion: chemical warfare in nature - Mitchell J. Greer; Gail W. T. Wilson; Karen R. Hickman; Stuart M. Wilson (Plant and Soil, 2014)

Effects of weather variation on a declining population of Slavonian Grebes Podiceps auritus - Steven R. Ewing; Stuart Benn; Neil Cowie; Lorraine Wilson; Jeremy D. Wilson (Journal of Ornithology, 2013)

Synthesizing mechanisms of density dependence in reef fishes: behavior, habitat configuration, and observational scale - J. Wilson White; Jameal F. Samhouri; Adrian C. Stier; Clare L. Wormald; Scott L. Hamilton; Stuart A. Sandin (Ecology, 2010)
Coral and rocky reef fish populations are widely used as model systems for the experimental exploration of density‐dependent vital rates, but patterns of density‐dependent mortality in these systems are not yet fully understood. In particular, the paradigm for strong, directly density‐dependent (DDD) postsettlement mortality stands in contrast to recent evidence for inversely density‐dependent (IDD) mortality. We review the processes responsible for DDD and IDD per capita mortality in reef fishes, noting that the pattern observed depends on predator and prey behavior, the spatial configuration of the reef habitat, and the spatial and temporal scales of observation. Specifically, predators tend to produce DDD prey mortality at their characteristic spatial scale of foraging, but prey mortality is IDD at smaller spatial scales due to attack‐abatement effects (e.g., risk dilution). As a result, DDD mortality may be more common than IDD mortality on patch reefs, which tend to constrain predator foraging to the same scale as prey aggregation, eliminating attack‐abatement effects. Additionally, adjacent groups of prey on continuous reefs may share a subset of refuges, increasing per capita refuge availability and relaxing DDD mortality relative to prey on patch reefs, where the patch edge could prevent such refuge sharing. These hypotheses lead to a synthetic framework to predict expected mortality patterns for a variety of scenarios. For nonsocial, nonaggregating species and species that aggregate in order to take advantage of spatially clumped refuges, IDD mortality is possible but likely superseded by DDD refuge competition, especially on patch reefs. By contrast, for species that aggregate socially, mortality should be IDD at the scale of individual aggregations but DDD at larger scales. The results of nearly all prior reef fish studies fit within this framework, although additional work is needed to test many of the predicted outcomes. This synthesis reconciles some apparent contradictions in the recent reef fish literature and suggests the importance of accounting for the scale‐sensitive details of predator and prey behavior in any study system.

Ultrasound for the Visualization and Quantification of Tumor Microcirculation - F. Stuart Foster; Peter N. Burns; David H. Simpson; Stephanie R. Wilson; Donald A. Christopher; David E. Goertz (Cancer and Metastasis Reviews, 2000)

A model of deposition and embolization of proteins and platelets on biomaterial surfaces - R. Scott Wilson; Abraham Marmur; Stuart L. Cooper (Annals of Biomedical Engineering, 1986)